The Library as a Digital Scholarship Hub - Abrigo, Christine; Labangon, Donna Lyn (Qualitative and Quantitative Methods in Libraries; Vol 10 No 4 (2021): December issue 2021, 2022)
With libraries now expected to be online and clients assuming that academic information resources are available and accessible publicly on the Internet anytime, the digital environment provided opportunities for the libraries to mature in their learning support for their school communities. This had been made even more pronounced when the COVID-19 pandemic affected the world over, moving all services and programs to shift heavily to the digital environment. While advanced libraries have been prominently embedding Library 4.0 in their learning support systems, the pandemic pushed many, if not all, libraries to consider developmental directions involving the heavy use of digital technologies in scholarship. This study aimed at exploring the digital scholarship (DS) service opportunities in libraries by means of benchmarking on the DS services and practices of the top higher education institution libraries in Asia in 2020, which endeavors to serve as baseline in coming up with a proposed DS hub development plan for Philippine academic libraries. The descriptive survey design using website investigation to screen data was employed, drawing up an instrument to contextualize the DS services mined from these websites, then categorized based on the determined and desired DS services environment. A DS services scan of the libraries of top-ranking Asian universities with that of the Philippines' best were mapped to get a perspective of the status of the latter's DS services, providing insights in coming up with a DS program plan. Data revealed that while leading Asian university libraries have moved away from the traditional types of services, content and framework, its Philippine counterparts' services were deemed emerging. Subject expertise upskilling among librarians in the fields of data research management, data services and digital technologies, as well as an intensified librarian engagement in DS partnerships and projects in the academic community were seen as opportunities for a responsive DS service. The output of this study has potential use in guiding Philippine academic libraries in coming up with their own framework and roadmap towards instituting their own DS services hub, to leverage learning support in their respective communities.